Antimicrobial and antioxidant activities from leaves and roots of (Elephantopus Scaber L.) extracted using different solvents - Mohammed, Mohammed Riyadh (School of Bioprocess Engineering, 2017)
The expectation of this research will cover the extract from the roots and leaves of Elephanthopus scaber using different type of solvent (water , ethyl alcohol and acetone) and also determine the effect of the extracts on different types of bacteria and fungi. The bacteria used in this study are Escherichia coli and Streptococcus pyogenes, Salmonella typhimurium, Staphylococcus aureus, Klebsiella pneumoniae and Fungus Condida Albican. Elephanthopus scaber extracts will also be investigated on the effect of free radical. The extract that gave the highest effect from the leaves and roots extract will be further tested for bioactive compounds using Gas Chromatography Mass Spectrometry (GC-MS).